On-Membrane Digestion Technology for Muscle Proteomics - Ohlendieck, Kay (Journal of Membrane and Separation Technology, 2013)
High-resolution two-dimensional gel electrophoresis and in-gel digestion are routinely used for large-scale protein separation and peptide generation in mass spectrometry-based proteomics, respectively. However, the combination of isoelectric focusing in the first dimension and polyacrylamide slab gel electrophoresis in the second dimension is not suitable for the proper separation of integral proteins and high-molecular-mass proteins. In addition, in-gel trypsination may not result in a high degree of efficient digestion levels for the production of large numbers of peptides in the case of certain protein species. The application of gradient one-dimensional gel electrophoresis and on-membrane digestion can overcome these technical problems and be extremely helpful for the comprehensive identification of proteins that are underrepresented in routine two-dimensional gel electrophoretic approaches. This review critically examines the general application of on-membrane digestion techniques in proteomics and its recent application for the identification of very large integral membrane proteins from skeletal muscle by mass spectrometry. This includes the discussion of proteomic studies that have focused on the proteomic characterization of the membrane cytoskeletal protein dystrophin from sarcolemma vesicles and the ryanodine receptor calcium release channel of the sarcoplasmic reticulum from skeletal muscle.